Amelioration of age-dependent increase in oxidative stress markers in male mice by extract of Potentilla fulgens. (3rd May 2016) - Saio, Valrielyn; Syiem, Donkupar; Sharma, Ramesh; Dkhar, Jameris
Abstract : Objective : To investigate the effect of Potentilla fulgens extract on lipid peroxidation and antioxidant status in male mice as a function of age. Methods : Eighteen-month-old Swiss albino male mice were administered the dichloromethane-methanol extract of P. fulgens (250 mg/kg b.w.) on alternate days via intraperitoneal route for a period of 14 days. Lipid peroxidation and activities of catalase (CAT) and glutathione peroxidase (GPx1) in liver and kidney were measured and serum oxygen radical absorbance capacity (ORAC) assay was estimated. Phytochemical analysis of P. fulgens extract using high performance thin layer chromatography (HPTLC) was carried out with gallic acid, quercetin, catechin, and epicatechin as markers. Results : Significant increase in level of thiobarbituric acid-reactive substances (TBARS), decreased GPx1, and CAT activities as well as reduction in ORAC were observed in 18-month-old mice as compared to that of 2-month-old mice. Treatment with P. fulgens extract significantly lowered TBARS level, ameliorated CAT, and GPx1 activities in liver and kidney and improved serum ORAC in aging mice. HPTLC studies revealed well resolved bands of P. fulgens extract containing epicatechin and catechin. Discussion : This study showed that P. fulgens is a potent antioxidative agent, which can emerge as a promising candidate in alleviating the age-associated oxidative stress and related diseases.